Tahap Perkembangan dan Pola Asuh Anak Usia 9-12 Tahun dalam Persepektif Islam - Perdiansyah Perdiansyah; Slamet Widodo (Jurnal Penelitian Pendidikan, 2021)
Islam is a very perfect religion. All aspects of life have been arranged in great detail. No exception to the stage of development and parenting of children aged 9-12 years. But unfortunately part of Muslims today do not know that Islam has set out in such detail the stages of development and parenting of children aged 9-12 years. Therefore, it is necessary to research on the stages of development and parenting of children aged 9-12 years in an Islamic perspective. It aims to provide reference material or reading material to parents and educators to educate their children Islamically. This study uses the literature review method by collecting data from various main sources originating from the Alquran, Alhadis, articles, and other relevant secondary sources. The results of this study are in the form of material or reading material that can be used as a reference for educating children Islamically.